Robotic Bootcamp 2023 attracts students to explore STEM fields - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
PEKAN, 21 August 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), in collaboration with Sekolah Kebangsaan Assunta Convent, for the first time organised the Professor Turun Padang Programme with the concept of Robotic Bootcamp 2023 which will last for three days starting today.